Spatial transcriptomics reveal basal sex differences in supraoptic nucleus gene expression of adult rats related to cell signaling and ribosomal pathways - Dianna H. Nguyen; Victor Duque; Nicole Phillips; André Souza Mecawi; J. Thomas Cunningham (Biology of Sex Differences, 2023)
Abstract Background The supraoptic nucleus (SON) of the hypothalamus contains magnocellular neurosecretory cells that secrete the hormones vasopressin and oxytocin. Sex differences in SON gene expression have been relatively unexplored. Our study used spatially resolved transcriptomics to visualize gene expression profiles in the SON of adult male (n = 4) and female (n = 4) Sprague-Dawley rats using Visium Spatial Gene Expression (10x Genomics). Methods Briefly, 10-μm coronal sections (~ 4 × 4 mm) containing the SON were collected from each rat and processed using Visium slides and recommended protocols. Data were analyzed using 10x Genomics’ Space Ranger and Loupe Browser applications and other bioinformatic tools. Two unique differential expression (DE) analysis methods, Loupe Browser and DESeq2, were used. Results Loupe Browser DE analysis of the SON identified 116 significant differentially expressed genes (DEGs) common to both sexes (e.g., Avp and Oxt), 31 significant DEGs unique to the males, and 73 significant DEGs unique to the females. DESeq2 analysis revealed 183 significant DEGs between the two groups. Gene Ontology (GO) enrichment and pathway analyses using significant genes identified via Loupe Browser revealed GO terms and pathways related to (1) neurohypophyseal hormone activity, regulation of peptide hormone secretion, and regulation of ion transport for the significant genes common to both males and females, (2) Gi signaling/G-protein mediated events for the significant genes unique to males, and (3) potassium ion transport/voltage-gated potassium channels for the significant genes unique to females, as some examples. GO/pathway analyses using significant genes identified via DESeq2 comparing female vs. male groups revealed GO terms/pathways related to ribosomal structure/function. Ingenuity Pathway Analysis (IPA) identified additional sex differences in canonical pathways (e.g., ‘Mitochondrial Dysfunction’, ‘Oxidative Phosphorylation’) and upstream regulators (e.g., CSF3, NFKB complex, TNF, GRIN3A). Conclusion There was little overlap in the IPA results for the two different DE methods. These results suggest sex differences in SON gene expression that are associated with cell signaling and ribosomal pathways.